PENGARUH PEMUPUKAN TERHADAP PRODUKSI DAN MUTU SERAIWANGI - Ansyarullah Ansyarullah; Emmyzar Emmyzar; Yaya Rubaya; Herman Herman; Daswir Daswir (Buletin Penelitian Tanaman Rempah dan Obat, 2006)
The Effect of fertilizer to citronella productionIn supporting the development of cit-ronella crops in Indonesia, so the increasing of crop productivities must be done. Fer-tilizing of the organic fertilizer is given to the crops is hoped to increase the fresh leaves production and high oil yield of citronella crops. The research of fertilizing effects of citronella production was concucted in the experimental garden in Laing, Solok, at 0.90 hectare areas. The location is 450 metres above the sea level with Red Yellow Podzolic of  the soil type. The reasearch was studied since January to December 2005. The expe-rimental design is Randomized Block Design with 5 treatments and 9 replications was used, those are whitout fertilizing, 0.50 kg lime/clump/6 month, 2.00 kg manure/clump/6 month, 0.50 kg compost/clump/6 month, and 2.00 kg manure plus 0.50 kg lime/clump/6 month. The result shows that fertilizing is given significant effect in the second and third harvest. The treatment of 2 kg manure plus 0.50 kg lime per 6 month produces the growth, fresh leaf production, and oil production of citronella which are the hig-hest. Up to the third harvest, manure plus lime can to increase the production of fresh leaf as big as 63.75% and oil production of citronella 36.20%. The content and quality of citronella oil which are produced, is the best and it is above the standard quality of Indo-nesian export.